2020
DOI: 10.20944/preprints202004.0321.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plants as a Prospective Source of Natural Anti-viral Compounds and Oral Vaccines Against COVID-19 Coronavirus

Abstract: The proposal of novel drugs and approaches for effective treatment of the novel coronavirus is a necessity after the quick outbreak of the disease. Since the commencement of the coronavirus spread, enormous efforts have been made to protect, alleviate and cure the disease, though no specific treatment has been approved. While there have been convincing results in the use of chemical drugs and interferon therapy, such therapeutic approaches have various drawbacks and lack the required performance for the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
0
19
0
2
Order By: Relevance
“…Lectins, the carbohydrate-binding proteins from Nicotiana tabacum, Allium porrum, and Utrica dioica were found to be significantly potential for slowing down the viral invasion and propagation to 50% (EC50) after applying the inhibitory concentrations (less than 1.3 µg/ mL) of pure extract of lectins (Yonesi and Rezazadeh, 2020). These compounds are the defense proteins in plants that can perform like immunologic receptors, and therefore could be marked for treating COVID-19 patients.…”
Section: Phenolics Flavonoids Polyphenols and Othersmentioning
confidence: 99%
“…Lectins, the carbohydrate-binding proteins from Nicotiana tabacum, Allium porrum, and Utrica dioica were found to be significantly potential for slowing down the viral invasion and propagation to 50% (EC50) after applying the inhibitory concentrations (less than 1.3 µg/ mL) of pure extract of lectins (Yonesi and Rezazadeh, 2020). These compounds are the defense proteins in plants that can perform like immunologic receptors, and therefore could be marked for treating COVID-19 patients.…”
Section: Phenolics Flavonoids Polyphenols and Othersmentioning
confidence: 99%
“…it's been con irmed that the PLPro and 3CLPro of the SARS-Cov and SARS-Cov2 are conserved. [8] Additionally, it's observed that there's a 76.10% identity between the mentioned viruses. Supported, it's expected that the results of the studies about the SARS-Cov might imply for research within the SARS-Cov2 to a high degree.…”
Section: The Current Methods Of Latest Coronavirus Treatmentmentioning
confidence: 99%
“…Plant"s immunity is a highly sophisticated system that can efficiently notice and disable the invading pathogens by a variety of tackles using intracellular receptor proteins. Many plant secondary metabolites are known to inhibit the effects of specific enzyme proteins essential for the propagation of different viruses (Yonesi & Rezazadeh, 2020). The essential oils targeting lipid-envelop and the polyphenols targeting viral protein are active against free viruses whereas the intercalating alkaloids inhibit the replication of viruses inside the host cell.…”
Section: Natural Products Against Sars-cov and Sars-cov-2mentioning
confidence: 99%